2016
DOI: 10.1136/bjsports-2016-096276
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of the effects of football heading

Abstract: We provide the first meta-analytical review of football heading effects aggregated from multiple studies and extended findings from a recent systematic review of the effects of football heading. Our analysis indicates no overall effect for heading a football on adverse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 48 publications
1
58
0
1
Order By: Relevance
“…Football is the only sport, in which players purposefully use the head to play the ball. 1 In recent years, short-and long-term consequences of playing football and the effect of heading on brain structure and function have been debated in professional football, [1][2][3][4][5][6][7][8] but more specifically in youth players. [9][10][11][12][13][14] In detail, four systematic reviews on the effects of football heading found no overall effect for heading on adverse outcomes; the consequences of repetitive heading to be unclear and various methodological shortcomings limit the evidence for persistent effects on brain structure/function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Football is the only sport, in which players purposefully use the head to play the ball. 1 In recent years, short-and long-term consequences of playing football and the effect of heading on brain structure and function have been debated in professional football, [1][2][3][4][5][6][7][8] but more specifically in youth players. [9][10][11][12][13][14] In detail, four systematic reviews on the effects of football heading found no overall effect for heading on adverse outcomes; the consequences of repetitive heading to be unclear and various methodological shortcomings limit the evidence for persistent effects on brain structure/function.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In detail, four systematic reviews on the effects of football heading found no overall effect for heading on adverse outcomes; the consequences of repetitive heading to be unclear and various methodological shortcomings limit the evidence for persistent effects on brain structure/function. 3,4,6,8 The consensus statement of the head injury summit described that acute or chronic neurocognitive effects from heading are elusive, also due to different research methodologies. 5 Other research on retired football players and heading may suggest that changes are reversible or that heading may not be as harmful as commonly thought.…”
Section: Introductionmentioning
confidence: 99%
“…The first studies on the topic were conducted in the early 1990s by Tysvaer and Lochen (1991), who found mild to severe neuropsychologic deficits in former soccer players compared to a control group, with a higher prevalence of impairment in "typical headers". However, more recently, two systematic reviews on the topic involving mostly active soccer players found no convincing evidence for this association (Kontos et al, 2017;Tarnutzer, Straumann, Brugger, & Feddermann-Demont, 2017). Interestingly, both meta-analyses noted that studies involving more senior or retired athletes were more likely to report adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Der kürzlich veröffentlichte systematische Review von Maher et al (2014) bestätig-te den bisherigen Stand der Forschung, dass der Einfluss des Kopfballspiels auf kognitive Fähigkeiten der Fußballspieler unklar ist [36]. Eine weitere Metaanalyse aus dem Jahre 2016 bestätigte zusätzlich, dass aktuell keine ungünstigen Folgen durch das Kopfballspiel nachzuweisen sind [31]. Speziell die schwache Methodik der vorliegenden Studien zu diesem Thema ist von Tarnutzer et al (2016) geschlussfolgert worden, wobei speziell der Nachweis, dass bestimmte klinisch-kognitive oder radiologisch-strukturelle Veränderungen am Gehirn nur sehr schwach mit dem Kopfballspiel und seiner Frequenz und Intensität in Zusammenhang gebracht werden können [54].…”
Section: Kopfballspiel Und Folgen Für Die Spielerunclassified